Tropical Rain forests of India-their Management and Regeneration - Rai, S. N. (Indian Forester, 1989)
Tropkal Rain Forests in India are found in three regions; the Western Ghats, the Northeast region and the Andamans and Nicobar islands. They are comparable in several respects yet they have their characteristic differences in floristics and composition. These forests ecosystems are very fragile in nature. They have been rather worked heavily in the past and have not regenerated very successfully in most cases. The delicate balance of light and shade requirement of the spp. That occur in these forests is a key factor in their regeneration. Two of the successful systems of regeneration are the Andaman Canopy Lifting System and the Aided Natural Regeneration. The forest of the three regions have been broadly described and their past management has been generally discussed. A suggestion has been made for their regeneration and restocking.